Infection risk reduction program on pathogens in high school and collegiate athletic training rooms - LaBelle, M. W.; Knapik, D. M.; Arbogast, J. W.; Zhou, S.; Bowersock, L.; Parker, A.; Voos, J. E. (Sports Health: A Multidisciplinary Approach, 2020)
Background: Athletic training rooms have a high prevalence of bacteria, including multidrug-resistant organisms, increasing the risk for both local and systematic infections in athletes. There are limited data outlining formal protocols or standardized programs to reduce bacterial and viral burden in training rooms as a means of decreasing infection rate at the collegiate and high school levels. Hypothesis: Adaptation of a hygiene protocol would lead to a reduction in bacterial and viral pathogen counts in athletic training rooms. Study Design: Cohort study. Level of Evidence: Level 3. Methods: Two high school and 2 collegiate athletic training rooms were studied over the course of the 2017-2018 academic year. A 3-phase protocol, including introduction of disinfectant products followed by student-athlete and athletic trainer education, was implemented at the 4 schools. Multiple surfaces in the athletic training rooms were swabbed at 4 time points throughout the investigation. Bacterial and viral burden from swabs were analyzed for overall bacterial aerobic plate count (APC), bacterial adenosine triphosphate activity, influenza viral load, and multidrug-resistant organisms such as methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant enterococcus (VRE). Results: Overall bacterial load, as measured by APC, was reduced by 94.7% (95% CI, 72.6-99.0; P = 0.003) over the course of the investigation after protocol implementation. MRSA and VRE were found on 24% of surfaces prior to intervention and were reduced to 0% by the end of the study. Influenza was initially detected on 25% of surfaces, with no detection after intervention. No cases of athletic training room-acquired infections were reported during the study period. Conclusion: A uniform infection control protocol was effective in reducing bacterial and viral burden, including multidrug-resistant organisms, when implemented in the athletic training rooms of 2 high schools and 2 colleges. Clinical Relevance: A standardized infection control protocol can be utilized in athletic training rooms to reduce bacterial and viral burden.